Design of programmable hardware security modules for enhancing blockchain based security framework - Devika Kalathil Nandalal; Ramesh Bhakthavatchalu (Institute of Advanced Engineering and Science, 2023)
Globalization of the chip design and manufacturing industry has imposed significant threats to the hardware security of integrated circuits (ICs). It has made ICs more susceptible to various hardware attacks. Blockchain provides a trustworthy and distributed platform to store immutable records related to the evidence of intellectual property (IP) creation, authentication of provenance, and confidential data storage. However, blockchain encounters major security challenges due to its decentralized nature of ledgers that contain sensitive data. The research objective is to design a dedicated programmable hardware security modules scheme to safeguard and maintain sensitive information contained in the blockchain networks in the context of the IC supply chain. Thus, the blockchain framework could rely on the proposed hardware security modules and separate the entire cryptographic operations within the system as stand-alone hardware units. This work put forth a novel approach that could be considered and utilized to enhance blockchain security in real-time. The critical cryptographic components in blockchain secure hash algorithm-256 (SHA-256) and the elliptic curve digital signature algorithm are designed as separate entities to enhance the security of the blockchain framework. Physical unclonable functions are adopted to perform authentication of transactions in the blockchain. Relative comparison of designed modules with existing works clearly depicts the upper hand of the former in terms of performance parameters.